PENGARUH WORK LIFE BALANCE, MOTIVASI KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. BANK PEMBANGUNAN DAERAH JAWA TIMUR TBK. CABANG UTAMA SURABAYA - Halimatus Sakdiyah; Sumiati (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aims to analyze the influence of work-life balance, work motivation, and communication on employee performance at PT Bank Pembangunan Daerah Jawa Timur Tbk. Main Branch Surabaya, both partially and simultaneously. The research background is the phenomenon of declining performance indicated by a 12% turnover rate, 3.2% decrease in customer satisfaction, and 15% increase in task completion delays. The study employs a quantitative approach with a survey method involving 78 respondents selected using Proportionate Stratified Random Sampling. Data collection used Likert scale questionnaires and was analyzed using multiple linear regression with SPSS. The results show that work-life balance has no significant effect on employee performance. Work motivation has a significant positive effect on employee performance. Communication has a significant positive effect on employee performance with the most dominant influence. Simultaneously, all three variables significantly influence employee performance